Utilization of Granulated Blast Furnace Slag in Cement Mortar: Performance Analysis Against M-Sand - Ms. Bandhavya G B; Ms. Lavanya H D; Mr. Mohana H S; Mr. Theju R K; Ms. Shilpa J; Ms. Madhushree C, (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2024)
This study aims to explore the feasibility of incorporating Granulated Blast Furnace Slag (GBFS) as a sustainable alternative to manufactured sand (M-Sand) in cement mortar, to enhance both environmental sustainability and mechanical performance. The research involves a systematic investigation where M-Sand is progressively replaced by GBFS at varying levels of 10%, 20%, 30%, 40%, and 50%. The effects of these replacements are evaluated through a series of tests that focus on the mortar’s physical properties, as well as its compressive and tensile strengths. Experimental results reveal that replacing 30% of M-Sand with GBFS produces the most favorable outcomes, with the compressive strength of the mortar exceeding that of the control mix by 12% after 28 days. The tensile strength also showed marked improvements at this replacement level. However, when the replacement level exceeds 30%, both compressive and tensile strengths begin to diminish, indicating that excessive substitution may adversely affect the mortar’s structural integrity. The findings of this study provide valuable insights into the optimal use of GBFS in cement mortar, demonstrating that a 30% substitution not only enhances strength characteristics but also contributes to more sustainable construction practices by reducing reliance on natural sand resources. This research supports the potential of GBFS as a viable material for improving the environmental profile and durability of cement-based materials.